Biological characteristics of the leser giant flying squirrels - Viet, Tran Hong; Chien, Le Van (Academia Journal of Biology, 2015)
After preliminary locating the distribution area of the leser giant flying squirrels in Vietnam, the article provides some research results on biological characteristics of the squirrels as follows: Appearance: the article elaborates on the outer appearance, the size, the colour as well as the skull size of the flying squirrels. Habitat: the leser giant flying squirrels inhabit only in primitive forests; they build their nest in the unobstrusive hollows on tall trees, sometime on the high fork branches in secret places. Activities: the leser giant flying squirrels are active mainly at night; the time of their activities is staged into two phases: phase 1 from 7 pm to 12 pm; phase 2 from 3 am to 5 am. Their fullest activities are from 8 pm to 9.30 pm. Foods: The main foods of the lesser giant flying squirrels are seasonal, grains and fruits. Their favorite food is grains rich of starch. In spring, they resort to leaves and young shoots of various trees because of the rarity of fruits. Breeding: the leser giant flying squirrels have 2 farrows once a year, 1 to 2 babies each time. The first farrow is from March to May, the second one is from September to January next year. Number of squirrels: the number of the leser giant flying squirrels is now shrunken and they are not positively protected. They are ranked as endangered species (E) according to Vietnam Red Book standard.